Tantalum carbide composite coating and preparation method and application thereof

By introducing a tantalum carbide-carbon composite coating into the tantalum carbide coating, the in-situ reaction between the porous carbon coating and the tantalum-containing raw materials is used to generate a tantalum carbide-carbon composite coating, which solves the mismatch problem caused by the difference in thermal expansion coefficient between the coating and the graphite matrix, and improves the thermal shock resistance and adhesion of the coating.

CN118851797BActive Publication Date: 2025-04-15HUNAN UNITED SEMICON TECH CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202410893297.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-04
Publication Date
2025-04-15
Estimated Expiration
2044-07-04

AI Technical Summary

Technical Problem

In the prior art, the difference in the thermal expansion coefficient between the tantalum carbide coating and the graphite matrix causes microcracks or cracks to occur in the coating, affecting the coating performance.

Method used

A composite coating consisting of a tantalum carbide coating on the surface and inside and inside is used to react in situ with the porous carbon coating and the tantalum-containing raw materials in the pore to form a tantalum carbide-carbon composite coating, whose thermal expansion coefficient is between the functional layer and the substrate, as a transition layer.

Benefits of technology

It effectively alleviates the thermal mismatch problem between the coating and the substrate, improves the thermal shock resistance of the coating, enhances the adhesion between the coating and the substrate, and extends the service life of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004928226690000011
    Figure HDA0004928226690000011
  • Figure HDA0004928226690000012
    Figure HDA0004928226690000012
  • Figure HDA0004928226690000021
    Figure HDA0004928226690000021
Patent Text Reader

Abstract

The present invention relates to the field of ceramic coatings, and in particular to a tantalum carbide composite coating and a preparation method and application thereof. The tantalum carbide composite coating includes a tantalum carbide coating from the surface to the inside and a tantalum carbide-carbon composite coating; the tantalum carbide-carbon composite coating is obtained by in-situ reaction of a porous carbon coating and a tantalum-containing raw material in the pores. The present invention roughens the graphite surface by carbon spraying on a graphite substrate. During the CVD deposition process, the tantalum pentachloride raw material will not only react with the carbon source to deposit a tantalum carbide coating, but also the gas source will also penetrate into the pores of the carbon coating and react with the carbon coating in situ to a certain extent to form a C-TaC transition layer, which not only effectively alleviates the mismatch problem caused by the difference in thermal expansion coefficients, but also enhances the adhesion between the coating and the substrate to a certain extent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of ceramic coatings, and in particular to a tantalum carbide composite coating and a preparation method and application thereof. Background Art

[0002] The production of SiC single crystals not only relies on sophisticated growth technology, but also faces the challenges of high temperatures exceeding 2400°C during the growth process and the impact of the growth environment. This process places extremely high demands on the purity and durability of production equipment, especially key components such as graphite trays and graphite crucibles. Since these graphite components are very easy to introduce trace impurities, their purity must be precisely controlled below 1ppm to avoid contamination of SiC single crystals.

[0003] In order to meet this challenge, a coating that can withstand high temperatures and block contamination must be applied to the surface of the graphite parts. Tantalum carbide (TaC) performs well in this regard. As a transition metal carbide with excellent physical and chemical properties, it has an extremely high melting point of 3880°C, and its physical and chemical properties at high temperatures are very stable. It can withstand direct contact with SiC and graphite without reacting. More importantly, TaC can serve stably in a variety of harsh chemical environments including hydrogen (H2), ammonia (NH3), monosilane (SiH4) and silicon (Si), and effectively prevents substrate corrosion. It is an ideal coating material for graphite parts used for SiC single crystal growth. By using TaC coating, the production quality and yield of SiC single crystals can be significantly improved, further promoting the development and application of semiconductor technology.

[0004] Prior art CN115948721B discloses a method for preparing tantalum carbide coating by CVD method; it relates to the field of tantalum carbide coating preparation; the specific steps of the method are as follows: pre-treat the substrate material; place the pre-treated substrate material in the reaction chamber of the CVD furnace, start the vacuum pump, pump the pressure in the furnace to below 100Pa, stop the vacuum pump, fill argon, let it stand, start the vacuum pump again, pump the pressure in the furnace to below 30Pa; heat to reach the deposition temperature, and keep warm; start the evaporation device, set the temperature and pressure, sublimate the tantalum salt into a gaseous state, introduce argon as a carrier gas, carry the gaseous tantalum salt to a mixing tank, and mix it evenly with hydrogen and propylene; the mixed gas enters the CVD furnace, heats, controls the gas pressure, deposits, stops introducing gas, stops heating, cools, and obtains a tantalum carbide coating. The tantalum carbide coating prepared by the invention has high mechanical properties and excellent high temperature corrosion resistance and thermal shock resistance. However, since the thermal expansion coefficients of the graphite substrate and the coating of the method are very different, the relevant thermal expansion coefficient data are also listed in the invention, which may cause microcracks or cracks in the coating and affect the performance of the coating.

[0005] Prior art CN 106699228 A discloses a method for preparing a low-cost tantalum carbide coating: first, the substrate is pretreated, and then a suspension is prepared using tantalum carbide, a sintering aid, an adhesive and a solvent, and the suspension is evenly sprayed or brushed on the surface of the substrate, and finally the substrate sprayed or brushed with the coating is preheated and sintered, so that a layer of tantalum carbide coating with uniform thickness and dense structure can be obtained on the substrate. The invention can coat a layer of TaC coating with a completely dense structure on the surface of the substrate, and the coating can isolate and protect the surface of the substrate to a great extent; it can be used for the preparation of high-performance coatings for devices or components for crystal and semiconductor production, to prevent the surface particles of the device or component from entering the crystal during crystal growth, thereby causing crystal defects. However, the wet method for preparing tantalum carbide coatings usually has through holes, which makes it difficult to prepare a high-density coating and cannot ensure uniformity. At the same time, it is also limited by the difference in thermal expansion coefficients between the substrate and the coating, which causes microcracks and cracks in the coating, affecting the coating performance.

[0006] Prior art CN 112374891 A discloses a graphite base plate surface gradient TaC coating and its preparation method, including a graphite base plate substrate, the surface of the graphite base plate substrate is provided with a gradient TaC coating; the gradient TaC coating includes a TaC component and a C component, the content of the TaC component gradually increases from 0% to 100% from the inside to the outside, and the gradient distribution conforms to the y=ax linear equation law or conforms to the y=ax2 parabolic law distribution. The invention uses CVD dynamic co-deposition technology to achieve a gradient span of the TaC component content in the coating from 0-100%. Since the inner layer of the coating is a pyrolytic carbon layer, its thermal expansion coefficient is similar to that of the graphite substrate, and then gradually transitions, which can effectively improve the thermal matching difference between the coating and the substrate; at the same time, the soft C component structure and nanopores in the coating can effectively alleviate the thermal expansion of the TaC crystal to reduce the stress peak in the coating. However, the invention has the following problems: 1. Difficulty in component control: Multi-component co-deposition requires precise control of the flow rate and reaction conditions of different precursors to ensure uniform deposition of each component. However, the reactivity of different gases may be different, which makes it difficult to accurately control the proportion of components, affecting the uniformity and performance of the coating. 2. Complex process parameters: In order to obtain an ideal multi-component coating, it is necessary to accurately adjust a variety of process parameters, such as gas flow, temperature, pressure, etc. mentioned in the patent. The optimization process of these parameters is complex and time-consuming, which increases the difficulty and cost of the process. 3. There are mutual reactions and by-products: In a multi-component system, different precursors may react with each other undesirably to generate by-products (such as more free carbon or tantalum carbide, etc.). These by-products may contaminate the coating or form impurities on the surface of the substrate, affecting the performance and purity of the coating. 4. Multi-layer structures are difficult to control: In multi-component CVD co-deposition, it may be challenging to form multi-layer or gradient coatings. The thickness and composition uniformity of each layer need to be precisely controlled to achieve the desired performance, which places higher requirements on process design and control. 5. Repeatability and stability are difficult to guarantee: Since multi-component CVD co-deposition involves multiple precursors and complex reaction conditions, it is difficult to ensure the consistency and stability of each deposition process.

[0007] Prior art CN 114853507 B discloses a composite carbon material and its preparation method and application. The composite carbon material can be used to make a tray for MOCVD equipment, including a carbon substrate and a composite coating arranged on the surface of the carbon substrate. The composite coating includes a silicon carbide composite layer, a silicon carbide tantalum carbide composite layer and a tantalum carbide layer stacked in sequence from the inside to the outside. The preparation method includes: (1) in-situ preparation of a silicon carbide nanowire layer on a carbon substrate, and then depositing silicon carbide after the preparation to form a silicon carbide composite layer; (2) depositing a silicon carbide tantalum carbide composite layer on the surface of the silicon carbide composite layer; (3) depositing a tantalum carbide layer on the surface of the silicon carbide tantalum carbide composite layer. The invention improves the stability of the carbon substrate, expands the scope of application and application scenarios, solves the problem of thermal mismatch, improves the bonding strength of the coating, and increases the service life; and effectively reduces the production cycle and production cost, and can effectively realize large-scale industrial production.

[0008] Prior art CN 117164363 B discloses a high-temperature composite material and a preparation method thereof. The high-temperature composite material includes a substrate and a continuous phase composite coating of hafnium carbide / tantalum carbide-silicon carbide arranged on the surface of the substrate. The preparation method includes: (1) pressing hafnium carbide powder on the surface of the substrate to obtain a green body, and sintering the green body to obtain a green body with a porosity of 35% to 45%; (2) chemically vapor co-depositing the green body to form a continuous phase composite coating of hafnium carbide / tantalum carbide-silicon carbide on the surface of the green body, thereby obtaining a high-temperature composite material. The high-temperature composite material obtained by the invention has excellent high-temperature comprehensive performance, high Young's modulus, high thermal conductivity, low thermal expansion coefficient, and good high-temperature mechanical properties, and has good thermal shock resistance and excellent erosion resistance. It is an ideal structural material for use in aerospace, semiconductor and other fields.

[0009] Prior art CN 104651771 A relates to a high temperature resistant and ablation resistant tantalum carbide composite coating and a preparation method thereof, wherein the tantalum carbide composite coating is composed of a TaC main phase and a SiC second phase, wherein the content of the SiC second phase is 5 to 30 vol.%. The coating material has a low ablation mass loss rate in a harsh environment of high temperature flame and air flow scouring, shows good ablation resistance, and significantly improves the ablation resistance of the TaC coating.

[0010] However, although the above three inventions use silicon carbide-tantalum carbide composite layers to solve the thermal mismatch problem, silicon carbide is difficult to use as a transition layer in a higher temperature service environment. High temperatures will cause silicon carbide to decompose and soften, thereby rendering the functional coating ineffective. Summary of the invention

[0011] The purpose of the present invention is to provide a tantalum carbide composite coating and a preparation method and application thereof, so as to solve the mismatch problem between the coating and the substrate due to the difference in thermal expansion coefficient.

[0012] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0013] A tantalum carbide composite coating comprises a tantalum carbide coating from the surface to the inside and a tantalum carbide-carbon composite coating; the tantalum carbide-carbon composite coating is obtained by in-situ reaction of a porous carbon coating and a tantalum-containing raw material in the pores.

[0014] Since the substrate is graphite, the thermal expansion coefficients of carbon and the substrate are close. At the same time, carbon can react in situ with tantalum-containing raw materials to generate a tantalum carbide-carbon composite coating, whose thermal expansion coefficient is between the functional layer and the substrate and can serve as a transition. Other materials, such as silicon carbide and hafnium carbide, have thermal expansion coefficients far different from those of graphite. Moreover, the transition layers of silicon carbide and hafnium carbide are mainly used for epitaxy and cannot be used for semiconductor crystal growth. The tantalum carbide composite coating of the present invention is mainly used for semiconductor crystal growth. Crystal growth and epitaxy are two processes required in the semiconductor manufacturing industry. The temperature required for crystal growth exceeds 2400°C, while the temperature required for epitaxy is only below 1500°C, and the melting point of silicon carbide is much lower than 2400°C.

[0015] In one preferred embodiment, the thickness of the tantalum carbide coating is 20-100 μm; the thickness of the tantalum carbide-carbon composite coating is 10-50 μm.

[0016] If the transition layer is too small, it cannot effectively alleviate the difference in thermal expansion coefficients between the substrate and the coating, resulting in greater stress at the interface, which can cause problems such as cracking and peeling of the coating. If the transition layer is too thick, it may cause stress concentration at the interface, thereby increasing the risk of cracking or peeling of the coating. An overly thick transition layer means more material consumption, which increases costs. In addition, the transition layer is designed to achieve a gradual change between different layers. If it is too thick, the transition will not be significant enough, affecting the performance of the overall material. Manufacturing a thick transition layer requires more complex processes and longer time, which increases production difficulty and cost.

[0017] If the outer coating is too thick, it will cause: 1. Weight and size: Too thick outer coating will increase the total weight of the coating system, and will also cause some key dimensions of the product to exceed the standard. 2. Cost increase: Too thick TaC outer layer means more material consumption and higher processing costs, which is not conducive to cost control. 3. Uneven performance: Too thick outer coating may cause uneven stress distribution inside the coating, affecting its mechanical properties and durability. 4. Heat treatment problems: Thicker coatings may cause uneven heat distribution during heat treatment, which in turn affects the microstructure and performance of the coating.

[0018] If the outer coating thickness is too small, it will cause: 1. Insufficient protection: A TaC outer coating that is too thin may not provide sufficient protection, which may cause the graphite substrate to be exposed to the environment, increasing the risk of corrosion, wear or other damage. 2. Reduced durability: A thinner TaC outer coating is easily worn or damaged during long-term use, reducing the overall life and performance of the coating.

[0019] The present invention also claims a method for preparing the tantalum carbide composite coating, comprising the following steps:

[0020] S1, brushing or spraying a carbon-containing precursor slurry on the surface of a graphite substrate, and then heat-treating it under an inert atmosphere to obtain a graphite substrate containing a porous carbon coating;

[0021] S2. Placing the graphite substrate containing the porous carbon coating in a CVD deposition furnace, introducing a tantalum-containing raw material and a carbon source, and performing deposition to obtain the tantalum carbide composite coating.

[0022] In a preferred embodiment, the graphite substrate is pretreated before spraying.

[0023] In a preferred embodiment, the pretreatment is: grinding, cleaning and drying the graphite substrate to obtain a graphite substrate with a clean surface.

[0024] In a preferred embodiment, the density of the graphite substrate is 1.7-2.3 g / cm 3 , thermal expansion coefficient is 5.0~7.0×10 -6 ·K -1 .

[0025] The density and thermal expansion coefficient of graphite represent the properties of the selected substrate. Too large or too small will affect the overall performance of the coating.

[0026] In a preferred embodiment, the pretreatment is: grinding the graphite substrate and then performing ultrasonic cleaning for 20-40 minutes, followed by drying at 80-100° C. for 50-80 minutes.

[0027] In a preferred embodiment, the carbon-containing precursor slurry comprises 20-60 parts of carbon raw material, 0.5-5 parts of dispersant and 35-85 parts of solvent in parts by weight.

[0028] When the mass of the dispersant is too low, the dispersibility and fluidity will be affected, making it difficult to disperse the particles, resulting in uneven dispersion or obvious precipitation. When the mass of the dispersant is too high, it will lead to the formation of a high viscosity system, affecting the spraying or coating effect.

[0029] If the quality of carbon raw materials is too low, the coating spraying uniformity will be poor or the coating cannot be formed completely. If it is too much, it will cause uneven dispersion and affect the spraying effect.

[0030] In a preferred embodiment, the carbon raw material is one or more of graphite, pyrolytic carbon, carbon black, and graphene.

[0031] In a preferred embodiment, the dispersant is a surfactant, preferably at least one of a polymer surfactant, polyvinyl alcohol, polyvinyl pyrrolidone, polyethylene glycol, and oleic acid.

[0032] In a preferred embodiment, the solvent is one or more of deionized water, alcohol solvents, ether solvents, alkane solvents, ester solvents, amine solvents, and aromatic solvents.

[0033] In a preferred embodiment, the particle size of the carbon-containing precursor slurry is 1-10 μm.

[0034] If the particle size is too large, the coating will have large gaps and roughness, which will reduce the material performance. If the particle size is too small, the coating will form large internal stress, which will cause the coating to crack or peel off easily during use.

[0035] In a preferred embodiment, the preparation method of the carbon-containing precursor slurry is: the carbon raw material, the dispersant and the solvent are uniformly mixed and then ball-milled for 4 to 20 hours to obtain the obtained product.

[0036] The length of ball milling time affects the effect of particle refinement. If the ball milling time is too long, it will lead to over-grinding of materials, too fine particles, and even problems such as sticking and clogging. If the ball milling time is too short, the materials are not fully ground and the expected grinding effect cannot be achieved.

[0037] In a preferred embodiment, the diameter of the ball milling medium is 0.1-5 mm.

[0038] The function of ball milling is to refine particles. The size of ball milling media will affect the degree of refinement and particle uniformity. Too large a size will cause uneven friction and reduce efficiency. Too small a size will cause accumulation.

[0039] In a preferred embodiment, the ball milling medium is one of stainless steel balls, cemented carbide balls, glass balls or agate balls.

[0040] In a preferred embodiment, the heat treatment temperature is 600-1500° C. and the time is 1-5 hours.

[0041] The main function of heat treatment is to volatilize organic solvents and dispersants. If the temperature is too low, it is difficult to achieve the desired volatilization effect, and if the temperature is too high, it will cause unnecessary energy loss and may produce by-products such as carbon black.

[0042] In a preferred embodiment, the porosity of the porous carbon coating is 10-30%.

[0043] Too low a value will result in the reaction gas being unable to fully penetrate into the carbon coating, while too high a value will result in excessive TaC deposition and the transition layer being unable to fully play its role.

[0044] Based on the wet preparation method used in the present invention, the coating sprayed by the method exhibits appropriate porosity due to the evaporation of the solvent. Appropriate porosity is achieved by controlling the mass fraction of the solute and the proportion of the dispersant.

[0045] In a preferred embodiment, the tantalum-containing raw material is TaCl5.

[0046] In a preferred embodiment, the source is one or more of methane, acetylene, ethylene and propylene.

[0047] In a preferred embodiment, the ratio of Ta atoms to C atoms in the tantalum-containing raw material and the carbon source is 1:1 to 1.2.

[0048] Excess Ta will cause the formation of by-products such as Ta2C, and excess C will lead to the formation of free carbon.

[0049] In one preferred embodiment, the deposition process is as follows: placing a graphite substrate containing a porous carbon coating in a CVD deposition furnace, evacuating the vacuum, filling with argon gas for cleaning for 10 to 30 minutes, and heating to 1500 to 2000°C; fully mixing the tantalum-containing raw material and the carbon source with the carrier gas and evaporating them, and passing them into the reaction chamber for coating deposition; then stopping heating and ending the gas introduction, cooling, and obtaining the tantalum carbide composite coating.

[0050] In a preferred embodiment, the deposition process is as follows: the vacuum degree is less than 100 Pa, the carrier is argon or H2, the deposition pressure is 2000-10000 Pa, and the evaporation temperature is 180-250°C.

[0051] The present invention also claims to protect the use of the tantalum carbide composite coating in preparing semiconductor crystal growth.

[0052] The beneficial effects of the present invention are:

[0053] The porous structure of the carbon coating can not only increase the surface roughness of the substrate, but also an in-situ reaction will occur between the tantalum source and the carbon coating to generate a C-TaC layer structure. The substrate-composite coating structure not only alleviates the thermal mismatch problem between the coating and the substrate, effectively improves the thermal shock resistance of the coating, but also plays a pinning role, enhances the adhesion of the coating, and increases the service life of the product. Compared with a single tantalum carbide coating, it will not produce crack accumulation and through holes, and the coating thickness can be freely designed.

[0054] The process control of the present invention is convenient. The graphite surface is roughened mainly by carbon spraying on the graphite substrate, and the surface of the carbon coating presents a porous structure with a large porosity. During the CVD deposition process, the tantalum pentachloride raw material will not only react with the carbon source to deposit the tantalum carbide coating, but the gas source will also penetrate into the pores of the carbon coating and react with the carbon coating to a certain extent in situ to form a C-TaC transition layer. The thermal expansion coefficient increases continuously from the substrate to the outer coating, which is a link between the above and the following, and not only effectively alleviates the mismatch problem caused by the difference in thermal expansion coefficient, but also plays a pinning role, which enhances the adhesion between the coating and the substrate to a certain extent, making the coating less likely to peel off and cause failure, and preventing the cracks from further extending. Compared with a single tantalum carbide coating, crack accumulation and through holes will not be generated, and the coating thickness can be freely designed. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] Figure 1 The structure of the tantalum carbide composite coating of Examples 1-4;

[0056] Figure 2 The appearance of the tantalum carbide composite coating of Examples 1-4;

[0057] Figure 3 is the SEM image of the coating of Comparative Example 1;

[0058] Figure 4 is the SEM image of the coating of Comparative Example 2;

[0059] Figure 5 This is the SEM image of the coating of Comparative Example 3. DETAILED DESCRIPTION

[0060] The present invention is further described in detail below in conjunction with specific embodiments.

[0061] Example 1

[0062] A method for preparing a tantalum carbide / tantalum carbide-carbon composite coating is as follows:

[0063] Matrix pretreatment: select density of 1.85g / cm 3 , the thermal expansion coefficient is 5.5×10 -6 ·K -1Graphite was used as the substrate. After the surface stains were polished off, it was placed in an ultrasonic cleaner for cleaning for 20 minutes, placed in an oven at 80-100℃ for drying for 60 minutes, and then temporarily stored.

[0064] Precursor configuration: Select polyvinyl alcohol as the dispersant and ethanol as the solvent, and evenly disperse the graphite powder in the solvent by heating and stirring to obtain a suspension. The mass fraction of the dispersant is 0.5wt%, the mass fraction of the graphite powder is 20wt%, and the remainder is the solvent. Put the suspension into a ball mill, add 5mm agate balls and mill for 8h to obtain a precursor solution (particle size 1μm).

[0065] Preparation of carbon coating: The prepared precursor liquid is loaded into the spray gun and sprayed on the surface of the graphite substrate with a spray thickness of 20 μm. After spraying, the sample is first placed in an oven at 80°C for drying, and then placed in a high-temperature furnace at 600°C under an argon atmosphere for 5 hours to obtain a carbon coating with a thickness of 20 μm and a porosity of 20%.

[0066] Preparation of TaC-C coating: Load the graphite substrate material with carbon coating into the CVD furnace, turn on the vacuum pump to reduce the vacuum degree to below 100 Pa, fill with argon gas for cleaning for 30 minutes, heat the furnace body to the process temperature of 1600 ° C, turn on the tantalum source evaporation device, the evaporation temperature is 180 ° C, use H2 or Ar as the carrier gas to evaporate TaCl5, and propylene as the carbon source. TaCl5 and C atoms are introduced into the mixing tank at a ratio of 1:1.2, and after being fully mixed with argon and H2, they enter the reaction chamber and are deposited under a deposition pressure of 2000 Pa. Deposition is performed for 3 hours, and the deposition thickness is 50 μm. After the deposition is completed, stop heating and stop the gas introduction, and wait until the furnace temperature drops to room temperature before taking it out of the furnace to obtain tantalum carbide / tantalum carbide-carbon composite coating.

[0067] [Example 2]

[0068] A method for preparing a tantalum carbide / tantalum carbide-carbon composite coating is as follows:

[0069] Matrix pretreatment: select density of 1.85g / cm 3 , the thermal expansion coefficient is 6×10 -6 ·K -1 The graphite was used as the substrate. After the surface stains were polished off, it was placed in an ultrasonic cleaner for cleaning for 20 minutes, placed in an oven, dried at 80-100℃ for 60 minutes, and then temporarily stored.

[0070] Precursor configuration: oleic acid is selected as the dispersant and ethanol is selected as the solvent. The graphite powder is uniformly dispersed in the solvent by heating and stirring to obtain a suspension. The mass fraction of the dispersant is 5wt%, and the mass fraction of the graphite powder is 60%. The suspension is placed in a ball mill, and 5mm agate balls are added and ball milled for 20 hours to obtain a precursor solution (particle size 1μm).

[0071] Preparation of carbon coating: The prepared precursor liquid is loaded into the spray gun and sprayed on the surface of the graphite substrate with a spray thickness of 20 μm. After spraying, the sample is first placed in an oven for drying, and then placed in a high-temperature furnace at 1500°C under an argon atmosphere for 1 hour to obtain a carbon coating with a thickness of 20 μm and a porosity of 10%.

[0072] Preparation of TaC-C coating: Load the treated graphite substrate material into the CVD furnace, turn on the vacuum pump to reduce the vacuum degree to below 100 Pa, fill with argon gas for cleaning for 30 minutes, heat the furnace body to the process temperature of 1600 ° C, turn on the tantalum source evaporation device, the evaporation temperature is 180 ° C, use H2 or Ar as the carrier gas to evaporate TaCl5, and propylene as the carbon source. TaCl5 and C atoms are introduced into the mixing tank at a ratio of 1:1.2, and after being fully mixed with argon and H2, they enter the reaction chamber and are deposited under a deposition pressure of 2000 Pa. Deposition is performed for 3 hours, and the deposition thickness is 50 μm. After the deposition is completed, stop heating and end the gas introduction, and wait until the furnace temperature drops to room temperature before taking it out of the furnace to obtain a tantalum carbide / tantalum carbide-carbon composite coating.

[0073] [Example 3]

[0074] A method for preparing a tantalum carbide / tantalum carbide-carbon composite coating is as follows:

[0075] Matrix pretreatment: select density of 1.85g / cm 3 , the thermal expansion coefficient is 6×10 -6 ·K -1 The graphite was used as the substrate. After the surface stains were polished off, it was placed in an ultrasonic cleaner for cleaning for 20 minutes, placed in an oven, dried at 80-100°C for 60 minutes, and then temporarily stored.

[0076] Precursor configuration: polyethylene glycol is selected as the dispersant and ethane is selected as the solvent. The graphite powder is uniformly dispersed in the solvent by heating and stirring to obtain a suspension. The mass fraction of the dispersant is 2.5wt%, and the mass fraction of the graphite powder is 40%. The suspension is placed in a ball mill, and 5mm agate balls are added and ball milled for 20 hours to obtain a precursor solution (particle size 1μm).

[0077] Preparation of carbon coating: The prepared precursor liquid is loaded into the spray gun and sprayed on the surface of the graphite substrate with a spray thickness of 20 μm. After spraying, the sample is first placed in an oven for drying, and then placed in a high-temperature furnace at 1500°C under an argon atmosphere for 5 hours to obtain a carbon coating with a thickness of 20 μm and a porosity of 15%.

[0078] Preparation of TaC-C coating: Load the treated graphite substrate material into the CVD furnace, turn on the vacuum pump to reduce the vacuum degree to below 100 Pa, fill with argon gas for cleaning for 30 minutes, heat the furnace body to the process temperature of 1600 ° C, turn on the tantalum source evaporation device, the evaporation temperature is 180 ° C, use H2 or Ar as the carrier gas to evaporate TaCl5, and propylene as the carbon source. Let TaCl5 and C pass into the mixing tank at a ratio of 1:1.2, and enter the reaction chamber after being fully mixed with argon and H2, and deposit the coating under a deposition pressure of 5000 Pa. Deposition for 3 hours, the deposition thickness is 50μm. After the deposition is completed, stop heating and end the gas introduction, wait for the furnace temperature to drop to room temperature and then take it out of the furnace to obtain tantalum carbide / tantalum carbide-carbon composite coating.

[0079] Example 4

[0080] A method for preparing a tantalum carbide / tantalum carbide-carbon composite coating is as follows:

[0081] Matrix pretreatment: select density of 1.85g / cm 3 , the thermal expansion coefficient is 5.5×10 -6 ·K -1 The graphite was used as the substrate. After the surface stains were polished off, it was placed in an ultrasonic cleaner for cleaning for 20 minutes, placed in an oven, dried at 80-100°C for 60 minutes, and then temporarily stored.

[0082] Precursor configuration: Polyvinyl pyrrolidone is selected as the dispersant and ether is selected as the solvent. The graphite powder is uniformly dispersed in the solvent by heating and stirring to obtain a suspension. The mass fraction of the dispersant is 2.5wt%, and the mass fraction of the graphite powder is 40%. The suspension is placed in a ball mill, and 5mm agate balls are added and ball milled for 20 hours to obtain a precursor solution (particle size 5μm).

[0083] Preparation of carbon coating: The prepared precursor liquid is loaded into the spray gun and sprayed on the surface of the graphite substrate with a spray thickness of 20 μm. After spraying, the sample is first placed in an oven for drying, and then placed in a high-temperature furnace at 1500°C under an argon atmosphere for 5 hours to obtain a carbon coating with a thickness of 20 μm and a porosity of 20%.

[0084] Preparation of TaC-C coating: Load the treated graphite substrate material into the CVD furnace, turn on the vacuum pump to reduce the vacuum degree to below 100 Pa, fill with argon gas for cleaning for 30 minutes, heat the furnace body to the process temperature of 1600 ° C, turn on the tantalum source evaporation device, the evaporation temperature is 180 ° C, use H2 or Ar as the carrier gas to evaporate TaCl5, and propylene as the carbon source. Let TaCl5 and C pass into the mixing tank at a ratio of 1:1.1, and enter the reaction chamber after being fully mixed with argon and H2, and deposit the coating at a deposition pressure of 5000 Pa. Deposition for 3 hours, the deposition thickness is 50μm. After the deposition is completed, stop heating and end the gas introduction, wait for the furnace temperature to drop to room temperature and then take it out of the furnace to obtain tantalum carbide / tantalum carbide-carbon composite coating.

[0085] The appearance of the tantalum carbide / tantalum carbide-carbon composite coating obtained in Example 1 is as follows: Figure 2 The tantalum carbide / tantalum carbide-carbon composite coating obtained in Example 1 was subjected to SEM detection, and the results showed that in the tantalum carbide-carbon composite coating, tantalum carbide was uniformly deposited in the pores of carbon, presenting a uniform composite coating structure, and no separate carbon layer existed. The appearance structure of Examples 2-3 is also similar to that of Example 1.

[0086] Comparative Example 1

[0087] The substrate pretreatment is the same as in Example 1.

[0088] Preparation of TaC-C coating: Load the pretreated graphite substrate material into the CVD furnace, turn on the vacuum pump to reduce the vacuum degree to below 100 Pa, fill with argon gas for cleaning for 30 minutes, heat the furnace body to the process temperature of 1600 ° C, turn on the tantalum source evaporation device, the evaporation temperature is 180 ° C, use H2 or Ar as the carrier gas to evaporate TaCl5, and propylene as the carbon source. Let TaCl5 and C pass into the mixing tank at a ratio of 1:1.2, and enter the reaction chamber after being fully mixed with argon and H2, and deposit the coating at a deposition pressure of 20000 Pa. Deposition for 3 hours, the deposition thickness is 50 μm. After the deposition is completed, stop heating and end the gas introduction, wait for the furnace temperature to drop to room temperature and then take it out of the furnace to obtain the TaC coating.

[0089] Compared with Example 1, the only difference in Comparative Example 1 is that no carbon coating is prepared, and the TaC coating is directly deposited on the graphite substrate. After deposition, the coating is cracked due to the difference in thermal expansion coefficient. The SEM image of the coating prepared in Comparative Example 1 is as follows: Figure 3 shown.

[0090] Comparative Example 2

[0091] Compared with Example 1, the difference is that the mass fraction of graphite powder is 10%.

[0092] After spraying, the SEM image of the coating prepared in Comparative Example 2 is as follows: Figure 4As shown, it can be seen that the prefabricated carbon coating is not obvious and difficult to form a film. There is no obvious visible C-TaC layer after CVD deposition, and there are obvious air bubbles and through holes in the coating, which is difficult to alleviate the difference in thermal expansion coefficient.

[0093] Comparative Example 3

[0094] Compared with Example 1, the difference is that the mass fraction of graphite powder is 65%.

[0095] After spraying, the SEM image of the coating prepared in Comparative Example 3 is as follows: Figure 5 As shown in the figure, the viscosity of the preformed precursor liquid is large, and there are many obvious precipitates. The preformed carbon coating is in the form of obvious carbon particles with basically no binding force. After CVD, the TaC layer has poor film-forming properties, and most of it penetrates through the carbon layer into the graphite matrix.

[0096] Comparative Example 4

[0097] Compared with Example 1, the difference is that the mass fraction of the dispersant is 0.4 wt %.

[0098] The particles in the precursor solution are aggregated to form larger particle clusters, and the sedimentation rate is accelerated, which makes the adhesion of the carbon layer after spraying lower and the coating partially fall off or peel off.

[0099] Comparative Example 5

[0100] Compared with Example 1, the difference is that the mass fraction of the dispersant is 10wt%.

[0101] It has been characterized that too much dispersant leads to poor compatibility with TaC coating, loose coating structure and poor adhesion.

[0102] Comparative Example 6

[0103] Compared with Example 1, the difference is that no dispersant is added when preparing the precursor.

[0104] The precursor delaminated quickly after ball milling and could not be fully dispersed in the liquid. The sprayed coating had poor uniformity and could not form a film. As a result, the composite coating could not be prepared.

[0105] Comparative Example 7

[0106] Compared with Example 1, the difference is that the particle size of the prepared precursor is 20 μm.

[0107] After spraying, the prepared carbon coating has a porosity of 60%, has many through holes, and appears in obvious carbon granular form with basically no bonding force.

[0108] Comparative Example 8

[0109] Compared with Example 1, the difference is that the particle size of the prepared precursor is 0.5 μm.

[0110] After spraying, the porosity of the prepared carbon coating is 5%, and no obvious TaC-C transition layer can be formed.

[0111] Comparative Example 9

[0112] Compared with Example 1, the difference is that the ratio of Ta atoms to C atoms is controlled at 1:0.9.

[0113] After characterization, it was found that the coating had an obvious Ta2C phase, indicating that when the tantalum source was excessive, the coating would generate Ta2C by-product.

[0114] Comparative Example 10

[0115] Compared with Example 1, the difference is that the ratio of Ta atoms to C atoms is controlled at 1:1.5.

[0116] After characterization, it was found that the coating contained obvious amorphous free carbon, indicating that when the carbon source was excessive, the coating would generate free carbon and other amorphous by-products.

[0117] Comparative Example 11

[0118] Compared with Example 1, the difference is that the thickness of the tantalum carbide coating is 200 μm.

[0119] After serving at high temperatures, the tantalum carbide coating has large thickness and uneven internal stress, which causes obvious cracking of the coating and reduces its service life.

[0120] Comparative Example 12

[0121] Compared with Example 1, the difference is that the thickness of the tantalum carbide coating is 10 μm.

[0122] After characterization, it was found that the tantalum carbide coating had fine cracks, could not provide good protection, and the functional layer failed.

[0123] Comparative Example 13

[0124] Compared with Example 1, the difference is that the thickness of the tantalum carbide-carbon composite coating is 80 μm.

[0125] After characterization, it was found that there was a large stress concentration between different layers, resulting in more sealed pores and microcracks at the interface and coating failure.

[0126] Comparative Example 14

[0127] Compared with Example 1, the difference is that the thickness of the tantalum carbide-carbon composite coating is 5 μm.

[0128] After characterization, it was found that the transition layer was too thin to alleviate the thermal mismatch, which caused the tantalum carbide coating to crack and failed to provide good protection.

[0129] Comparative Example 15

[0130] Compared with Example 1, the difference is that the transition layer is silicon carbide.

[0131] The silicon carbide transition layer was prepared by chemical vapor deposition, with SiCl4 and CH4 as reaction gases, hydrogen as carrier gas, and Ar as protective gas. The thickness of the prepared transition layer was 50 μm by deposition at 1400°C for 30 minutes. After serving at 2400°C, the silicon carbide layer softened and the TaC functional layer failed.

[0132] The above is only a preferred embodiment of the present invention, and the protection scope of the present invention is not limited to the above embodiments. For those skilled in the art, improvements and changes obtained without departing from the technical concept of the present invention should also be regarded as the protection scope of the present invention.

Claims

1. A tantalum carbide composite coating, characterized in that: It includes a tantalum carbide coating from the surface to the inside and a tantalum carbide-carbon composite coating; the tantalum carbide-carbon composite coating is obtained by in-situ reaction of a porous carbon coating and a tantalum-containing raw material in the pores; the preparation method of the tantalum carbide composite coating includes the following steps: S1, brushing or spraying a carbon-containing precursor slurry on the surface of a graphite substrate, and then heat-treating it under an inert atmosphere to obtain a graphite substrate containing a porous carbon coating; S2, placing the graphite substrate containing the porous carbon coating in a CVD deposition furnace, introducing a tantalum-containing raw material and a carbon source, and depositing to obtain the tantalum carbide composite coating; The heat treatment temperature is 600-1500°C and the time is 1-5h; The carbon-containing precursor slurry is composed of 20-60 parts of carbon raw material, 0.5-5 parts of dispersant and 35 parts of solvent by weight; the carbon raw material is one or more of graphite, pyrolytic carbon, carbon black and graphene; the particle size of the carbon-containing precursor slurry is 1-10 μm; the porosity of the porous carbon coating is 10-30%; In the tantalum-containing raw material and carbon source, the ratio of Ta atoms to C atoms is 1:1 to 1.2; The thickness of the tantalum carbide coating is 20-100 μm; the thickness of the tantalum carbide-carbon composite coating is 10-50 μm.

2. The tantalum carbide composite coating according to claim 1, characterized in that: The dispersant is a surfactant.

3. The tantalum carbide composite coating according to claim 1, characterized in that: The dispersant is a polymer surfactant.

4. The tantalum carbide composite coating according to claim 1, characterized in that: The dispersant is at least one of polyvinyl alcohol, polyvinyl pyrrolidone, polyethylene glycol and oleic acid.

5. The tantalum carbide composite coating according to claim 1, characterized in that: The solvent is one or more of deionized water, alcohol solvents, ether solvents, alkane solvents, ester solvents, amine solvents, and aromatic solvents.

6. A method for preparing the tantalum carbide composite coating according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1, brushing or spraying a carbon-containing precursor slurry on the surface of a graphite substrate, and then heat-treating it under an inert atmosphere to obtain a graphite substrate containing a porous carbon coating; S2. Placing the graphite substrate containing the porous carbon coating in a CVD deposition furnace, introducing a tantalum-containing raw material and a carbon source, and performing deposition to obtain the tantalum carbide composite coating.

7. The method according to claim 6, characterized in that The graphite substrate is pretreated before spraying; the pretreatment is: grinding, cleaning and drying the graphite substrate; the density of the graphite substrate is 1.7-2.3 g / cm 3 , thermal expansion coefficient is 5.0~7.0×10 -6 ·K -1 .

8. The method according to claim 6, characterized in that The preparation method of the carbon-containing precursor slurry is as follows: the carbon raw material, the dispersant and the solvent are uniformly mixed and then ball-milled for 4 to 20 hours to obtain the obtained product.

9. The method according to claim 8, characterized in that The diameter of the ball milling medium is 0.1 to 5 mm; the ball milling medium is one of stainless steel balls, carbide balls, glass balls or agate balls.

10. The method according to any one of claims 6 to 9, characterized in that: The deposition process is as follows: placing a graphite substrate containing a porous carbon coating in a CVD deposition furnace, evacuating the vacuum, filling with argon gas for cleaning for 10 to 30 minutes, and heating to 1500 to 2000° C.; fully mixing a tantalum-containing raw material and a carbon source with a carrier gas, evaporating the mixture, and introducing the mixture into a reaction chamber for coating deposition; then stopping heating and ending the gas introduction, cooling the mixture, and obtaining the tantalum carbide composite coating.

11. Use of the tantalum carbide composite coating according to any one of claims 1 to 5 in the preparation of semiconductor crystal growth.

Citation Information

Patent Citations

  • High-temperature-resistant ablation-resistant tantalum carbide composite coating and preparation method thereof

    CN104651771A

  • Low-cost tantalum carbide coating preparation method

    CN106699228A

  • Graphite base disc surface gradient TaC coating and preparation method thereof

    CN112374891A

  • A composite carbon material, its preparation method and application

    CN114853507B

  • A method for preparing tantalum carbide coatings by CVD

    CN115948721B